ENHANCING JOB COMPETITIVENESS: HOW WORK READINESS MODERATES THE EFFECT OF UPSKILLING AMONG GEN Z STUDENTS - Muhammad Aliyyuddin Salim; Wahyu Eko Pujianto; Novi Handayani (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
In the face of the digital disruption era and rapid industrial transformation, students as future workers are required to have high competitiveness to be able to compete in the global job market. One strategy that can be implemented is through upskilling, which involves enhancing existing skills to align with industry demands. This study aims to analyze the impact of upskilling on the job competitiveness of Gen Z students in East Java and to test the moderating role of work readiness in this relationship. The theoretical foundation of this study is based on Human Capital Theory, which emphasizes the importance of investing in education and training to enhance individual productivity. This study employs a descriptive quantitative approach using a survey method via an online questionnaire administered to 310 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS 4.0). The results indicate that upskilling has a positive and significant impact on job competitiveness. However, work readiness does not significantly moderate this relationship. These findings suggest that although students have high work readiness, this does not always strengthen the impact of upskilling if it is not accompanied by relevant and contextual training tailored to the needs of the job market. Therefore, strategic integration between skill development and work readiness is essential to enhance students' competitive advantage in the digital job market. Keywords: upskilling, job competitiveness, work readiness, Gen Z students, Human Capital Theory